Use of accelerometry to investigate physical activity in dogs receiving chemotherapy. (5th October 2016) - Helm, J.; McBrearty, A.; Fontaine, S.; Morrison, R.; Yam, P.
Abstract : Objectives: To perform a preliminary study to assess whether single‐agent palliative or adjuvant chemotherapy has an impact on objectively measured physical activity in dogs. Methods: Fifteen dogs with neoplasia (treatment group) wore ActiGraph™ accelerometers for 5‐day periods before, during and after receiving single‐agent adjuvant or palliative chemotherapy. Mean 5‐day total physical activity and time spent in three different intensities of activity (sedentary, light‐moderate and vigorous) before, during and after receiving chemotherapy were compared to a group of 15 healthy dogs (control group). Results were also compared within the treatment group across time. Results: Prior to chemotherapy, treated dogs tended to be less active than control dogs. Treatment group dogs were slightly more active at restaging than they were prior to treatment but had similar activity levels to control dogs. Marked effects of chemotherapy on physical activity were not detected. Physical activity was slightly lower in treated dogs during chemotherapy when compared to control dogs but there was a slight increase in physical activity of treated dogs during chemotherapy when compared with pretreatment recordings. There was little change in the mean 5‐day total physical activity between treated dogs during chemotherapy and at restaging but a mild decrease in time spent sedentary and increase in time spent in light‐moderate activity at this comparison of time points. Clinical Significance: Single‐agent adjuvant or palliative chemotherapy had minimal impact on physical activity levels in dogs with neoplasia.